Inevitable Disaster for Türkiye: Earthquake and Nursing - Ilknur Yücel (Health and Technology Journal (HTechJ), 2023)
Disasters are natural, technological, or human-induced events that cannot be dealt with with the available means that cause physical, economic, and social losses in societies and nations. The most common disaster is an earthquake. Earthquake is vibrations arising from the incoming nuclei formed in the earth's crust that are felt in the upper layers of the earth by spreading in waves. The stronger the earthquake, the more destructive it is. It causes loss of life and property in individuals as soon as many people occur, especially earthquakes. To minimize the losses in this situation, the concept of disaster definition was introduced for nurses, who are professional members of the health profession. Disaster visualization: She is a disaster manager with knowledge of the nursing profession and a multidisciplinary team. The roles of images in disaster situations; pre-disaster, disaster moment, post-disaster, and pictures. Before the disaster, It is the preparation stage for the cells of the disaster before the disaster occurs. moment of disaster; Depending on the realization of the disaster, life-saving, first aid and emergency response are at the forefront. This study aims to find the knowledge of the occupation type related to the determination of the roles, duties, and responsibilities of the nurses, who are health professionals, in the earthquakes that occurred in Turkey. The extension of the courses in the field of earthquakes to the undergraduate programs of nurses, the holding of sessions such as congresses, symposiums, interviews, and panels with the field guarantees in-service support to the employees from the top positions, including their initiatives at the beginning.